Petrogenesis and tectonic settings of epithermal mineralization-related granites in the Xinchenggou area, NE China - Hao, Yi; Guo, Lingli; Feng, Yingming; Zhang, Hao; Somerville, Ian; Li, Sanzhong; Zhu, Junjiang (Frontiers in Earth Science, 2023)
The Xinchenggou area is located in the northeast part of the eastern segment of the Xingmeng orogenic belt (EXOB), NE China and has been demonstrated to be a promising exploration target for epithermal deposits. Although previous studies have shown that syenogranite and monzogranite occurring in the Xinchenggou area are promising in forming epithermal mineralization, the petrogenesis and geodynamic settings in which these granites were emplaced are still unclear. To address these problems, in this study detailed whole-rock major and trace element analyses for these granites were conducted. Combined with previously published data, we show that both syenogranite and monzogranite in the Xinchenggou area are high-K calc-alkaline and peraluminous with high SiO2. Their REE concentrations are low (ΣREE=72.35×10-6-217.64×10-6) and show obvious differentiation between LREE and HREE (LaN/YbN=2.74-11.37), with apparent Eu negative anomalies (δEu=0.14-0.83) and indistinctive Ce anomalies (δCe =0.96-1.11). Combined with petrographical observations, it is suggested that both syenogranite and monzogranite are (slightly fractionated) I-type granite. Nb/Ta ratios of syenogranite and monzogranite range from 6.18 to 26.33, indicating that the granitic magma was derived from the upper mantle or the lower crust. Both syenogranite and monzogranite were emplaced in a continental arc setting, which was related to the subduction of the Paleo-Pacific Plate beneath the Eurasian Plate during the Late Triassic to Early Jurassic.